2022
DOI: 10.3390/geohazards3010004
|View full text |Cite
|
Sign up to set email alerts
|

A Concise Appraisal of Cameroon’s Hazard Risk Profile: Multi-Hazard Inventories, Causes, Consequences and Implications for Disaster Management

Abstract: The paucity of a comprehensive document on Cameroon’s hazard/disaster risk profile is a limitation to the country wide risk assessment and adequate disaster resilience. This article narrows this gap by retrospectively exploring Cameroon’s hazard/disaster profile. This has been achieved through an investigative approach that applies a set of qualitative methods to derive and articulate an inventory and analysis of hazards/disasters in Cameroon. The findings indicate that Cameroon has a wide array and high incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Information-driven policies, as highlighted by Chen et al (2021), are imperative for DRR and sustainable development. Governance, identified as a DR driver, underscores the necessity for capacity building to enhance the effectiveness of human resources (Acharibasam & Datta, 2024), addressing concerns raised by Becker and van Niekerk (2015), Bang (2014Bang ( , 2022, about the deficiency of skilled DRR practitioners in Africa, which leads to delay in the translation of policies into actions.…”
Section: Optimized Hotspot Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Information-driven policies, as highlighted by Chen et al (2021), are imperative for DRR and sustainable development. Governance, identified as a DR driver, underscores the necessity for capacity building to enhance the effectiveness of human resources (Acharibasam & Datta, 2024), addressing concerns raised by Becker and van Niekerk (2015), Bang (2014Bang ( , 2022, about the deficiency of skilled DRR practitioners in Africa, which leads to delay in the translation of policies into actions.…”
Section: Optimized Hotspot Resultsmentioning
confidence: 99%
“…As a crucial factor for disaster recovery and adaptation, Marin et al (2021) advocate for the inclusion of such resilience components in DR assessments. Notably, acute shortage of skilled practitioners have been identified as a source of delay in translating good policies into actions (Bang, 2014(Bang, , 2022Becker & van Niekerk, 2015). Furthermore, Keating et al (2017) Within hotspots, as indicated by Shi et al (2016), the occurrences of hazards surpass coping capacities, resulting in increased vulnerabilities.…”
Section: Disaster Risks Drr and Sustainable Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the ranks of such displacements, individuals find it difficult to find jobs or livelihood activities to generate incomes for themselves thereby confirming findings of Nkongho (2018); Bang. and Balgah (2022) and Bang (2022) who reported that thousands of persons have been displaced with 80% of the people living in forests and bushes.…”
Section: The Current Level Of Displacementmentioning
confidence: 99%